Peningkatan Kualitas Guru di Sekolah Swasta melalui Program Pelatihan dan Pendampingan Berkelanjutan - Khoiruzzaim Kurniawan (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
This research aims to evaluate and improve the quality of teachers at MI Ma'arif NU Private Schools in Wonodadi District, Blitar Regency through the implementation of ongoing training and mentoring programs. This research uses a qualitative approach by collecting data through observation, interviews and analysis of related documents. The research results show that there is an urgent need to improve the quality of teachers in these schools. Therefore, this research develops and implements a structured training program and ongoing mentoring for teachers. This program is designed to accommodate the needs of individual and group teachers, with a focus on improving pedagogical competence, leadership, and the application of innovative approaches to learning. Continuous evaluation is carried out to monitor program progress and effectiveness. The research results show that the implementation of continuous training and mentoring programs can significantly improve the quality of teachers at the MI Ma'arif NU Private School, have a positive impact on learning performance, and encourage the development of teacher professionalism. This research contributes to the development of an educational model that focuses on improving the quality of human resources in private schools, with the hope of providing inspiration for similar educational institutions in efforts to improve the quality of education at the local and national level.